A novel B2O3/B4C-modified composite adhesive with wide operative temperature range for alumina fiber fabric bonding. Issue 5 (1st March 2021) - Liu, Peisen; Zhang, Xueying; Xue, Yunjia; Guo, Anran; Liu, Liachen
Abstract: A heat resistance adhesive with wide operative temperature range for bonding alumina fiber fabric was developed by organic-inorganic modification. The polyvinyl alcohol modified by B2 O3 generated a complex cross-linked network connected by B–O–C bonds, which can enhance the bonding strength of adhesive after heat-treatment from RT to 400 °C. Moreover, the addition of B4 C can enhance the bonding strength of adhesive after heat-treatment from 400 °C to 800 °C due to the formation of molten B2 O3 and borosilicate glass. Significantly, the appropriate addition of B4 C can make the adhesive form a denser structure without transforming the fracture mode of the bonding joints, which is conducive to enhance the strength performance of bonding joints after sintered at 800 °C. On the contrary, the excessive addition of B4 C will transform the fracture mode of the bonding joints into brittle fracture, which will degrade the strength performance of bonding joints.